Proceedings of the 12th Edition of the International Workshop on Smalltalk Technologies 2017
DOI: 10.1145/3139903.3139913
|View full text |Cite
|
Sign up to set email alerts
|

Debugging Cyber-Physical Systems with Pharo

Abstract: Cyber-Physical Systems (CPS) integrate sensors and actuators to collect data and control entities in the physical world. Debugging CPS systems is hard due to the time-sensitive nature of a distributed applications combined with the lack of control on the surrounding physical environment. This makes bugs in CPS systems hard to reproduce and thus to fix. In this context, on-line debugging techniques are helpful because the debugger is connected to the device when an exception or crash occurs. This paper reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In what follows we discuss the debugging experience of IDRA and TelePharo. Further details on the case study can be found in [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In what follows we discuss the debugging experience of IDRA and TelePharo. Further details on the case study can be found in [24].…”
Section: Resultsmentioning
confidence: 99%
“…Following Pacheco [30] and the survey from McDowell and Helmbold [25], we categorize debugging techniques in two big families: Offline Debugging and Online Debugging. 3 More information about the CPS application and its deployment can be found in [24].…”
Section: Online and Offline Debuggingmentioning
confidence: 99%
“…In regards to the original use-case [9], Collectors provided dynamic and non-intrusive instrumentations to observe the runtime. We use remote debuggers as a support to remotely control Collectors and get feedback from the collected objects.…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration, we used the Sensor Monitoring Application usecase [9]. It is a single threaded Pharo IOT application deployed on a Raspberry Pi 2 in which there is an unpredictable bug at runtime.…”
Section: The Sensor Monitoring Application Usecasementioning
confidence: 99%
“…The developer proceeds then to debug as if the application was originally a local application. In previous work, we successfully applied this approach to debugging long-running applications and cyber-physical systems [18,16]. Such a debugging technique suits Big Data applications since it allows production code running on a cluster to continue processing tasks while the failing tasks can be debugged in an external machine.…”
Section: Online Debugging Of Big Data Applicationsmentioning
confidence: 99%